Implementation of Green Construction in Jragung Dam Construction Project, Semarang - Firmawan, Ferry; Kuncoro, Ahmad Hakim Bintang; Budiningrum, Diah Setyati (Jurnal Teknik Sipil, 2023)
Global warming arises due to environmental damage that coincides with one of the causes of building construction projects. Hence, green construction is a solution to minimize the negative impact of development construction projects. This study aims to determine the application of green construction in the Jragung dam, Semarang construction project. Data collection was carried out through a questionnaire survey of respondents from 50 workers from 5 companies (contractors) involved in the construction of the Jragung dam, Semarang. Data analysis was carried out using statistical descriptive analysis methods. The results showed that in the Jragung dam construction project, Semarang, the contractors as the executors and persons in charge of the project had applied the green construction concept even though it has yet to be maximized. The application of green construction based on six assessment indicators has a percentage of 53%-98%. PT Wijaya Karya is a project contractor who has implemented Green construction with the highest percentage of 81%, followed by PT Wijaya Karya. Waskita Karya (79%) and PT Brantas Abipraya (77%), while the other two contractors are PT Pelita Nusa Perkasa (68%) and PT Basuki Rahmanta Putra (66%) is ranked in the bottom 2 in applying green construction in the Jragung dam construction project, Semarang.